Evaluación radiológica del tratamiento conservador de fracturas de radio distal en el Hospital Regional Docente De Trujillo. - Del Río Espinoza, Mario Sergio (2019)
Introduction: Distal radius fractures are frequent in Emergency Deparment. Radiological assessment is useful for diagnosis, treatment and monitoring. Objective: To compare the values of radial height, radial inclination, ulnar variance and dorsal inclination of distal radius fractures treated conservatively, at the initial injury and at definitive cast removal. Materials and methods: Observational and descriptive study. Data from the PA and lateral radiographs of 35 patients with unilateral closed distal radial fractures treated conservatively were used. T-Student and Wilcoxon tests were used. Results: A decreased in radial height, radial inclination and dorsal inclination, and ulnar variance increased was evidenced. Conclusions: There was a redisplacement of all radiological parameters studied. It was significant for radial shortening and dorsal inclination, the latter improved relatively but did not return to normal values.